Autologous Hematopoietic Stem Cell Transplants as a Treatment for Multiple Sclerosis - Mehta, Sonali; Kamal, Arhaan (The Meducator, 2025)
Multiple sclerosis (MS) presents through progressive loss of motor function due to the demyelination of axons throughout the nervous system. It is categorized as an autoimmune disease with a variety of subclassifications based on the recurrence of degenerative events. This review examines the efficacy of autologous hematopoietic stem cell transplantation (AHSCT) in reducing the symptoms related to MS compared to traditional disease-modifying therapies (DMTs) such as ocrelizumab and ofatumumab. Within current literature, AHSCT has shown success in increasing quality of life as well as halting degenerative events. In preliminary studies, AHSCT has shown greater improvement when used prior to DMTs. However, severe limitations hinder the availability of AHSCT, such as the risk of neuroablative illness, highly specific treatment criteria, and high costs. AHSCT is a promising treatment for alleviating MS symptoms, and necessary research on its long-term efficacy is currently underway.